Investigation of the gene Dynactin 2 (Dctn2) in regulating the frequency of asymmetric cell divisions during mouse preimplantation embryonic development, required to generate inner cells and drive successful cell lineage segregation and successful development - Kubíčková, Michaela (Jihočeská univerzita, 2018)
The aim of his study was to investigate the role of Dctn2 in mouse preimplantation embryonic development, specifically its effect on the first cell fate decision, when the number of cells increases from eight to sixteen.
Investigation of the gene Dynactin 2 (Dctn2) in regulating the frequency of asymmetric cell divisions during mouse preimplantation embryonic development, required to generate inner cells and drive successful cell lineage segregation and successful development
Keywords: mouse preimplantation embryonic development; dynactin subunit 2; mouse preimplantation embryonic development; dynactin subunit 2